2018
DOI: 10.1051/matecconf/201823202039
|View full text |Cite
|
Sign up to set email alerts
|

Study on forming process and spring back control of high strength sheet based on Dynaform

Abstract: The drawing process of a high strength steel part without blank holder force was numerically simulated based on Dynaform. In present investigation, the drawing velocity and velocity profile motion of punch was studied by simulating the drawing operation of high strength steel part. The results show that restricting drawing velocity and controlling velocity profile motion of punch could all reduce the spring back. The measure of restricting drawing velocity could reduce non-pressure forming spring back about 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The corrected bending has a smaller spring back than free bending. In the bending of the workpiece, the corrected force is small and the spring back force is large, and the increasing corrected force can reduce the spring back [11] . As shown in Figure 7, if the dies are not equipped with a correction die, the force limit of the panel veneer is small and the spring back angle is large after leaving the dies.…”
Section: Influencing Factors Of Bending Spring Back Phenomenon (1) Me...mentioning
confidence: 99%
“…The corrected bending has a smaller spring back than free bending. In the bending of the workpiece, the corrected force is small and the spring back force is large, and the increasing corrected force can reduce the spring back [11] . As shown in Figure 7, if the dies are not equipped with a correction die, the force limit of the panel veneer is small and the spring back angle is large after leaving the dies.…”
Section: Influencing Factors Of Bending Spring Back Phenomenon (1) Me...mentioning
confidence: 99%
“…They conducted a U-bending test to investigate the effect of servo press slide motion on 980-MPa high-strength steel and concluded that servo presses can be set to function with slide motion that varies within a single operation. In 2018, Liu 11 developed a drawing process for high-strength steel parts without blank holder force based on numerical simulation in Dynaform. They used simulations of high-strength steel to draw the velocity and corresponding profile motion of a punch and concluded that restricting the drawing velocity and controlling the velocity profile of the punch motion could reduce springback by approximately 31%.…”
Section: Introductionmentioning
confidence: 99%